Learning strategies, study behaviors, and academic performance among medical students in Jordan: A cross-sectional study - Wafaa A. Mahmoud; Ahmad A. Alrawashdeh; Khaled A. Mahmoud; Nasr N. Alrabadi; Ibrahim M. Hoja; Abdelrahman M. Qasaymeh; Abdulla M. AlKofahi; Mohammad M. Alsmadi; Basel A. Alnajjar (PLoS ONE, 2026)
Academic performance in medical education is influenced by multiple factors, including learning strategies and study behaviors. However, the extent to which these factors are associated with academic performance remains unclear. This study aimed to describe the frequency of learning strategies and examine their associations with academic performance among medical students, with emphasis on evidence-based strategies. A cross-sectional anonymous online survey was conducted among medical students at Jordan University of Science and Technology. Learning strategies were assessed using ten items rated as rarely, sometimes, or often. Composite indices were constructed for overall, evidence-based, and common/passive strategies. Academic performance was categorized as excellent, very good, or good or below. Group comparisons were performed using chi-square tests and ANOVA, and multivariable logistic regression identified factors associated with excellent performance. Among 556 respondents, 52.2% reported excellent performance. Evidence-based strategies showed a graded increase across performance groups and were independently associated with higher odds of excellent performance (aOR 1.47, 95% CI 1.16–1.86), whereas common/passive strategies were not. These findings suggest that evidence-based learning strategies are associated with better academic performance, supporting their potential role in medical education. However, the findings are exploratory rather than causal.